Simufilam suppresses overactive mTOR and restores its sensitivity to insulin in Alzheimer’s disease patient lymphocytes - Wang, Hoau-Yan; Pei, Zhe; Lee, Kuo-Chieh; Nikolov, Boris; Doehner, Tamara; Puente, John; Friedmann, Nadav; Burns, Lindsay H. (Frontiers in Aging, 2023)
Implicated in both aging and Alzheimer's disease (AD), mammalian target of rapamycin (mTOR) is overactive in AD brain and lymphocytes. Stimulated by growth factors such as insulin, mTOR monitors cell health and nutrient needs. We examined the effects of simufilam, a small molecule oral drug candidate for AD, on mTOR and its response to insulin in AD patient lymphocytes. Simufilam targets an altered conformation of the scaffolding protein filamin A (FLNA) found in AD brain and lymphocytes that induces aberrant FLNA interactions leading to AD neuropathology. Simufilam restores FLNA's normal shape to disrupt its AD-associated protein interactions. We show here that mTOR is overactive and its response to insulin is reduced in lymphocytes from AD versus healthy control subjects, illustrating another aspect of insulin resistance in AD. After oral administration of simufilam to AD subjects, lymphocytes showed normalized basal mTOR activity and improved insulin-evoked mTOR activation in mTOR complex 1, complex 2, and upstream and downstream signaling components (Akt, p70S6K and phosphorylated Rictor). Suggesting mechanism, FLNA interacts with the insulin receptor until dissociation by insulin; in AD lymphocytes, this linkage is elevated and its dissociation impaired. Simufilam improved the insulin-mediated dissociation. Additionally, FLNA's interaction with Phosphatase and Tensin Homolog deleted on Chromosome 10 (PTEN), a negative regulator of mTOR, is reduced in AD lymphocytes and improved by simufilam. Reducing mTOR's basal overactivity and its resistance to insulin represents another mechanism of simufilam to counteract aging and AD pathology. Simufilam is currently in Phase 3 clinical trials for AD dementia.